Tinjauan Kriminologi Dan Perlindungan Hukum Korban Kekerasan Seksual Terhadap Perempuan Dalam Rumah Tangga - Aldini Rizky Santoso; Ari Wibowo (Fakultas Hukum Universitas Islam Indonesia, 2024)
Every human being must have the desire to have a harmonious household and get love from family members. However, every family must have their own problems that cause disharmony among family members. The emergence of these problems can be a big thing in the form of violence against family members, where women are the targets of violence. One form of violence is domestic sexual violence. As a result, the Indonesian government issued UU RI Number 23 of 2004 concerning the Elimination of Domestic violencefollowed by UU RI Number 12 of 2022 concerning Crimes of Sexual Violence. The purpose of this research is to find out and analyze the factors that cause sexual violence against women victims in the household and the legal protection for women as victims of domestic sexual violence. The method used was empirical with a sociological approach. Research data were obtained from interviews with the Rifka Annisa WCC Yogyakarta. The results of this study are personality, economic and environmental factors which are factors of sexual violence against female victims in the household. As well as in providing legal protection the UU PKDRT and UU TPKS are felt to be less specific in implementing and providing protection and the rights of victims of sexual violence against women in the household. There needs to be concern between law enforcers and the public regarding this matter.